Threat or opportunity? An analysis of perceptions of cultured meat in the UK farming sector - Manning, Louise; Dooley, John J.; Dunsford, Illtud; Goodman, Michael K.; MacMillan, Tom C.; Morgans, Lisa C.; Rose, David C.; Sexton, Alexandra E. (Frontiers in Sustainable Food Systems, 2023)
The environmental and social impacts of cultured meat, and its economic viability, are contingent on its implications for food production and for agriculture. However, the implications of cultured meat production for farmers have not yet been thoroughly investigated and are poorly understood. The aim of this research was to engage with the farming sector in critically assessing cultured meat as a technology which could profoundly affect future farm livelihoods, land use, rural and farming communities and agricultural value chains. Ensuring farmers' voices, and potential 'counternarratives' inform the development of cultured meat is not only inclusive, but could identify unexpected impacts of this emerging technology and contribute to the framing of the social license of the industry developing them.Six focus groups were undertaken with 75 UK farmers from a variety of farming sectors and regions. Questions focused on what the term 'cultured meat' means to farmers, the potential impacts of cultured meat, and potential business scenarios arising for farmers. All meetings were recorded, transcribed, and thematically analyzed.Farmers expressed complex and considered reflections on cultured meat, raising several perceived opportunities and risks associated with the themes of 'ethics and affective' narratives, 'environmentbased' narratives, and 'socio-economic' narratives. Aspects of foci of power, food system control and transparency associated with cultured meat emerged from the conversations, as well as cultured meat's potential impacts on the environment and on jobs, farming/rural communities and connecting with the land.Globally, meat production underpins the livelihoods of many rural communities, so a transition to cultured meat is likely to have deep-seated ethical, environmental, and socio-economic impacts. Within the discourse on cultured meat the voices of farmers are often lost. While not claiming to be representative of all UK farming, this study engaged UK farmer perspectives as a way of starting the substantive process of greater stakeholder inclusion in cultured meat innovation pathways, and which should underpin responsible technology transitions in agriculture.